2018
DOI: 10.3168/jds.2018-15012
|View full text |Cite
|
Sign up to set email alerts
|

Freezing point and other technological properties of milk of the Polish Coldblood horse breed

Abstract: Mare milk is a valued and sought-after raw material for the production of innovative dairy products. The high demand, low supply, high price, and lack of accurate characterization of the milk of a given horse breed may provoke its deliberate fraudulent dilution. The aim of this work was to analyze the freezing point against a background of various selected technological parameters of Polish Coldblood mare milk. Research was carried out on multiparous Polish Coldblood mares from 5 to 8 yr of age with live weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…It has been shown in the literature that the fat content of mare's milk is lower than other species. The fat content (14.5 ±0.59) is similar to that reported by other authors for raw mare's milk (Cais-Sokolińska et al, 2018;Claeys et al, 2014;Salimei and Fantuz, 2012;Sansanwal et al, 2017). In our study, the lactose content 64.6 ±1.01 g/kg is comparable to that indicated by Potočnik et al (2011) for the same breed.…”
Section: Characteristics Of Mare's Milk Compositionsupporting
confidence: 91%
“…It has been shown in the literature that the fat content of mare's milk is lower than other species. The fat content (14.5 ±0.59) is similar to that reported by other authors for raw mare's milk (Cais-Sokolińska et al, 2018;Claeys et al, 2014;Salimei and Fantuz, 2012;Sansanwal et al, 2017). In our study, the lactose content 64.6 ±1.01 g/kg is comparable to that indicated by Potočnik et al (2011) for the same breed.…”
Section: Characteristics Of Mare's Milk Compositionsupporting
confidence: 91%
“…Cais-Sokolińska et al ( 2018) reported a higher crude protein level in milk from cold-blooded mares (2.42%) than that obtained in the present study, whereas Markiewicz-Kęszycka et al (2013) and Čagalj et al (2014) reported lower concentrations of crude protein in milk from cold-blooded horses: 1.55% and 1.76%, respectively. Cais-Sokolińska et al (2018) and Pieszka et al (2011) obtained similar density for milk from cold-blooded mares (1.037 kg/dm 3 ), while Hachana et al (2021) reported slightly lower density for milk from warm-blooded Arabian mares (1.031 kg/dm 3 ). Malacarne et al (2002) report that the energy value of horse milk is 480 kcal/100 g (390-550), compared to 677 kcal/100 g (650-700) for human milk and 674 kcal/100 g (650-712) for cow milk.…”
Section: Discussionmentioning
confidence: 88%
“…Czyżak-Runowska et al ( 2021) tested milk from 13 Polish Coldblood, Silesian, and Haflinger mares and found that its average fat content was 1.16%. Cais-Sokolińska et al (2018), analysing changes in the chemical composition of milk from Polish cold-blooded horses during 9-month lactation, found that the fat content remained similar (1.51% ± 0.01) from 30 to 210 days of lactation and then gradually decreased to 0.79% at 240 days and to 0.76% at 270 days. Even higher fat content (1.69%) was recorded in milk from 45 Arabian mares from Tunisia (Hachana et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studying of economic and useful traits of horses promotes the right choice of breed for these or those specific conditions. Results provide additional opportunities to increase horse breeding production [18].…”
Section: Resultsmentioning
confidence: 94%